Role of Extension Agencies in Dissemination of Technologies on Medicinal and Aromatic Plants and Needs for their Conservation through Peoples' Participation in Central India - Rai, Rajiv (Indian Forester, 2007)
The paper describes the role of extension agencies in dissemination of technology about utilization of medicinal and aromatic plants through individual contact, group contact and mass contact approaches of diffusion of technology pertaining to medicinal and aromatic plants and their parts used in herbal medicines in the states of Chhattisgarh and Madhya Pradesh in Central India. In Chhattisgarh, highest dissemination of technology is through Mass contact i.e. 40% of the diffusion of technology from State Forest Department to end users. The traditional and folk-healers disseminate the technology through its application to endusers and thus diffusion takes place by help of neighbours and friends visiting them or those who use herbal and aromatic plants for cure of diseases and are in their contact. In Madhya Pradesh, the end-users contact the extension agencies for knowing the technology, obtaining training needs to such agencies. The paper suggest that extension workers and agencies involved in dissemination of technology play a vital role in envisage and analyse the situation in which response of individuals may emerge . Many such plant species are over-exploited on account of their medicinal and aromatic value. In Central India many species suffer loss of genetic diversity and habitat loss hence conservation is essential for future use by coming generation. Hence extension workers and agencies should be ready and alert all the time, to use a series of channels of communication along with alternate approaches of extension techniques to motivate the users and convince them about the technology for their adoption : easily, quickly with maximum number of beneficiaries should utilize the technology on sustainable basis, as well as involve conservation of herbal plants in forest ecosystem.